Effects of the minimum wage on the dynamics of formal and informal employment in Brazil: building research hypotheses - Cardoso, Adalberto (2022)
The article proposes hypotheses about the relationship between minimum wage, formal employment, informal employment and occupational transitions in the Brazilian wage labor market. It contests the theory according to which the real increase in the minimum wage generates unemployment and/or informality, bringing evidence that, on the contrary, the minimum wage, from a certain level considered adequate by informal wage earners, attracts these workers, thereby reducing informality, particularly in contexts of expansion of formal employment, such as the one experienced by Brazil between 2003 and 2014. It also provides evidence that the minimum wage, by increasing in real terms, has a “drag effect” on the other wages of formal employees, whose values increase through mechanisms discussed in the text.